2020
DOI: 10.1111/sapm.12295
|View full text |Cite
|
Sign up to set email alerts
|

Optimal control of dengue epidemic outbreaks under limited resources

Abstract: In this paper, we reflect upon control intervention practices habitually exerted by healthcare authorities in tropical areas that suffer from incidental outbreaks of dengue fever, in particular, the city of Cali, Colombia. Such control interventions, principally based on the insecticide spraying, are carried out sporadically in order to overcome an ongoing epidemic or at least to reduce its size. It is worth pointing out that control actions of this type do not usually account for sufficient budget because epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…8 (f), it can be seen that the insecticide is maintained at full effort for 72 days before drastically reduces for the rest of the intervention. These results seem to be consistent with previous research [36] , [42] which found that the insecticide spraying alone had the effect of rapidly reducing the number of infectious humans, almost enabling eradication of disease.
Figure 8 Numerical results of the model using insecticide only.
…”
Section: Numerical Results Of the Control Problemsupporting
confidence: 92%
See 1 more Smart Citation
“…8 (f), it can be seen that the insecticide is maintained at full effort for 72 days before drastically reduces for the rest of the intervention. These results seem to be consistent with previous research [36] , [42] which found that the insecticide spraying alone had the effect of rapidly reducing the number of infectious humans, almost enabling eradication of disease.
Figure 8 Numerical results of the model using insecticide only.
…”
Section: Numerical Results Of the Control Problemsupporting
confidence: 92%
“…The use of the control for dengue infection as a prevention only has been considered in the work [33] , [41] . The control insecticide spraying only has been considered in dengue control model given in [42] . The use of both the control for dengue control in the population is considered in [36] , [43] .…”
Section: Optimal Control Problemmentioning
confidence: 99%
“…In optimal control approach, we use quadratic terms in the control variables to capture the nonlinear cost in the implementation of controls. This approach is rather conventional and has been frequently used in the epidemiological modelling including dengue modelling [11,13,26 approach to investigate the effects of vector control and vaccination on dengue transmission dynamics. They used quadratic terms in the control variables as to represent the nonlinear cost [23], which has been also used in the other work for the similar reason to investigate the dengue transmission dynamics in the presence of controls [11,13,26,15,23,39,40,12].…”
Section: Discussionmentioning
confidence: 99%
“…In optimal control approach, we use quadratic terms in the control variables to capture the nonlinear cost in the implementation of controls. This approach is rather conventional and has been frequently used in the epidemiological modelling including dengue modelling [11] , [13] , [26] , [15] , [23] , [39] , [40] , [12] . Rawson et al implemented optimal control approach to investigate the effects of vector control and vaccination on dengue transmission dynamics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation